PENGARUH MODEL NUMBERED HEADS TOGETHER TERHADAP HASIL BELAJAR IPA DI SD - Januardi, Anggie Eko; Rosnita, Rosnita; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research purposed to analyzed how was the influence of Number Heads Together approach in the Science learning improvement on the Fourth Grades Students of SDN 66 Pontianak. This research conducted experimental method;Quasi-Experimental with nonequevalent control group design. The population was all of the fourth grades students of SDN 66 Pontianak. 78 student were selected as the sample of this research, where it consits of 39 control group students and 39 experiment group students. Technique of data collecting was measurement technique with 45 multiple choice questions as the instrument. The findings of this research had the mean score of control group about 71,46 while the mean score of experimental group was 75,15. The result of hypothesis test (t-test) used t-test separated varian were tcount 1,93 and ttable 1,667 (significant level (alpa)) = 5% and dk = 7). It shower that tcount >ttable. So that Ha could be accepted. By this mean, there were the difference of learning result between the students with Number Heads Together learning and the students who had study without it. From the counting of effect size (Es), it was 0,31(moderate). It can be concluded that Number Heads Together give a high influence in Science learning on Fourth Grades Students of SDN 66 Pontianak.Key words : influences, number heads together approach , learning outcomes, science.